Post Traumatic Impaction of Maxillary Deciduous Central Incisor: A Case Report - Bahoz Himdad Majeed (Erbil Dental Journal)
Background and Objectives: Primary tooth impaction is a rare phenomenon when compared to permanent teeth impaction, particularly in upper front teeth. The problem could be either a physical blockage of the eruption or a malfunction of the eruption process.